2019
DOI: 10.1111/1440-1681.13190
|View full text |Cite
|
Sign up to set email alerts
|

Potential roles of Citrulline and watermelon extract on metabolic and inflammatory variables in diabetes mellitus, current evidence and future directions: A systematic review

Abstract: Objective Diabetes mellitus is a prevalent endocrine disorder worldwide. Citrulline is an α‐amino acid, which is abundant in watermelon, and a precursor of arginine and nitric oxide. Decreased bioavailability of nitric oxide is associated with insulin resistance. The present systematic review focused on the existing evidence of citrulline and watermelon extract effects on metabolic and inflammatory parameters in diabetes mellitus. Methods A systematic search of the databases PubMed, Scopus, EMBASE, ProQuest an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 118 publications
(285 reference statements)
0
14
1
Order By: Relevance
“…Watermelon has high levels of several micronutrients including citrulline. [23][24][25] Cell line and animal studies have shown decreases in tumor necrosis factor-alpha and IL-1 beta, which are proinflammatory; whereas, increases in IL-10, which is anti-inflammatory, has been found with administration of this micronutrient. 56,57 Among critically-ill adults, oral citrulline supplementation was found to lower concentrations of proinflammatory cytokines.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Watermelon has high levels of several micronutrients including citrulline. [23][24][25] Cell line and animal studies have shown decreases in tumor necrosis factor-alpha and IL-1 beta, which are proinflammatory; whereas, increases in IL-10, which is anti-inflammatory, has been found with administration of this micronutrient. 56,57 Among critically-ill adults, oral citrulline supplementation was found to lower concentrations of proinflammatory cytokines.…”
Section: Discussionmentioning
confidence: 99%
“…Emphasis was put on watermelon, which is abundant in certain key elements that have been shown to have antiinflammatory properties. [23][24][25] Weekly meal plans were designed to provide participants with 2 meals per day that incorporate watermelon. In each weekly class session, recipes containing watermelon were demonstrated and prepared.…”
Section: Intervention Design and Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Watermelon is a rich source of citrulline, although it contains other bioactive substances such as arginine, pectin and lycopene. Therefore, its antioxidant properties may be related to each or a combination of these compounds ( 37 ) .…”
Section: Discussionmentioning
confidence: 99%
“…However, You et al [97] reported that chronic Arg (1.5%) or CIT (1.66%) supplementation (in drinking water for 9 weeks) did not prevent or reduce renal injury in a model of type I diabetes in diabetic mice, despite greatly increasing kidney and plasma Arg levels. Finally, a recent systematic review concluded that CIT and watermelon extract may beneficially affect glycemic status and inflammation in diabetes mellitus, although studies on their antioxidant and hypolipidemic effects in diabetic patients are scarce [98].…”
Section: L-citrulline and Diabetesmentioning
confidence: 99%